A Market for Time: Fairness and Efficiency in Waiting Lines - Felix Oberholzer-Gee (Center for Research in Economics, Management and the Arts (CREMA), 2003)
In situations of excess demand, many firms use waiting lists to allocate products and services among their customers. The resulting allocation is likely to be inefficient, creating opportunities for Pareto improving trades among those who are waiting in line. Yet, in the queuing context, the trading of places is rare and inefficiencies often persist over time. In this paper, I report the results of a field experiment which allows randomly selected customers to earn up to 10 for letting a stranger cut in line. The higher the offer, the more likely it is that individuals let someone cut in. But while a majority agrees to wait longer, only a small minority accepts the monetary reward. Trading in this market is constrained by multiple social concerns. The obligation not to exploit situations of excess demand and efficiency considerations influence the willingness to let a stranger jump the queue.
Keywords: 330; Fairness; rationing; social norms